More Children Means More Tumours? We Can Do More to Protect the Health of Our Kids-A Call for a New Epidemiology That Can Change the World - Prisco Piscitelli; Alessandro Miani; Enrico Greco; Alessandro Distante; Francesco Schittulli; Adele Civino (MDPI AG, 2023)
In encyclopaedic dictionaries published until 1955, the word "tumour" was defined as an "occupational disease suffered by the workers of chemical industries", thus referring to a very specific cause [...]